FACILITATING THE ADULT LEARNING PROCESSES IN SECOND CHANCE EDUCATION : WHAT DO THE LATVIAN ADULT LEARNERS AND THEIR EDUCATORS THINK ABOUT ? - Surikova, Svetlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The paper aims at presenting the findings of the research on core competences of adult educators conducted in Latvia during the study "Identification and analysis of new challenges and solutions that have influence on engagement and reintegration of adults (18- 24 years) in lifelong learning" funded by ESF project "Support to research in educational field" (sub-activity 1.2.2.3.2.), No 011/0011/1DP/1.2.2.3.2/11/IPIA/VIAA/001. The adult educators and adult learners from the field of second chance education (evening shift schools) were involved in an online survey (2011-2012) using the research tool developed in the project “Qualified to Teach” − QF2TEACH. The main research results are analysed in order to identify the core competences of educators as adult learning facilitators and to compare the adult learners and their educators’ opinion concerning these competences within the domains: interpersonal behaviour and communication with learners, access and progression of learners, monitoring and assessment of learning processes.